2019
DOI: 10.1155/2019/5207958
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Methanol Extract ofMelastoma malabathricumL. Leaves following the Subacute and Subchronic Oral Consumptions in Rats and Its Cytotoxic Effect against the HT29 Cancer Cell Line

Abstract: Methanol extract of Melastoma malabathricum (MEMM) has been traditionally used by the Malay to treat various ailments. In an attempt to develop the plant as an herbal product, MEMM was subjected to the subacute and subchronic toxicity and cytotoxicity studies. On the one hand, the subacute study was performed on three groups of male and three groups of female rats (n = 6), which were orally administered with 8% Tween 80 (vehicle control group) or MEMM (500 and 1000 mg/kg) daily for 28 days, respectively. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Typical toxicity endpoints for long-term exposure studies are organ damage [16,17], tissue fibrosis [16,17], and hematological and biochemical parameters [15,18,19]. Subacute and subchronic toxicity assays are widely used to determine whether frequent exposure to a substance causes adverse effects [20]. Therefore, in order to better define the safety profile of RELP, SD rats were fed with RELP for 28 and 90 days; bodyweight, food intake, histopathology, and hematological and biochemical parameters were monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Typical toxicity endpoints for long-term exposure studies are organ damage [16,17], tissue fibrosis [16,17], and hematological and biochemical parameters [15,18,19]. Subacute and subchronic toxicity assays are widely used to determine whether frequent exposure to a substance causes adverse effects [20]. Therefore, in order to better define the safety profile of RELP, SD rats were fed with RELP for 28 and 90 days; bodyweight, food intake, histopathology, and hematological and biochemical parameters were monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Since M. malabathricum leaves, particularly MEMM, possess significant antioxidant and antiinflammatory activities as mentioned above, the plant's leaves/its extract was earlier proposed to also possess a chemopreventive activity based on the well-acknowledged link between oxidative stress, inflammation and carcinogenesis (Valko et al, 2007;Lu, 2007). Interestingly, in our earlier investigation using the in vitro model, MEMM was found to exert cytotoxic activity against the HT-29 colon cancer cell line (Kamsani et al, 2019). Taking this finding into consideration, the present study was designed to investigate on the potential of MEMM to attenuate colon carcinogenesis using the in vivo azoxymethane (AOM)-induced colon cancer in rat model.…”
Section: Introductionmentioning
confidence: 90%
“…Detailed procedure to prepare MEMM can be found in a report by Kamsani et al (2019). Briefly, the dried leaves powder of M. malabathricum (200g) was macerated in methanol (1:20 (w/v)) for 72 hours.…”
Section: Preparation Of Memmmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers reported that the SLE contains the phenolic compounds which be able to scavenge free radical and inhibit the oxidation process, as well as anti-bacteria both in vitro and in vivo assay (Alnajar et al, 2012;Alwash et al, 2014;Wong et al, 2012;Zakaria et al, 2011). Even, SLE does not cause any acute toxicity and safety (Alnajar et al, 2012;Alwash et al, 2014;Kamsani et al, 2019). For food purposes, Suharyanto et al (2019) noted that the maceration using water as a solvent also yielded SLE containing phenolic substances and could inhibit the bacteria growth.…”
Section: Introductionmentioning
confidence: 99%